Paradoxical undersensing of atrial electrograms during atrial fibrillation due to repeated activation of the quiet timer blanking interval: Case report and review of the literature. Issue 5 (13th January 2014) - Morishima, Itsuro; Sone, Takahito; Takami, Mitsuaki; Tsuboi, Hideyuki; Michitaka, Uesugi; Matsushita, Etsushi; Morita, Yasuhiro; Tsuji, Yoshinori
Abstract: This report describes a case of paradoxical atrial undersensing by a dual‐chamber pacemaker during paroxysmal atrial fibrillation. Undersensing of 5.6 mV atrial signals at a programmed sensitivity of 0.5 mV returned to normal sensing by decreasing atrial sensitivity to 1.0 mV. This uncommon phenomenon can be explained by a repeated activation of the quiet timer blanking interval. Knowledge of this phenomenon is important in the current pacemaker management to improve the accuracy of the diagnostic feature for atrial tachyarrhythmia burden and to avoid unnecessary lead revisions.